Effect of Health Counseling on Tinea Pedis on Farmers Attitudes in Prevention of Tinea Pedis in Sukodono Village, Karangrejo District, Tulungagung Regency, 2017 - Farida, Farida (Journal of Global Research in Public Health, 2019)
Tinea Pedis (athlete's foot) is a water flea disease caused by fungi Trichophyton, Epidermophyton, and Microsporum. Tinea pedis often attacks farmers and washers. In 2015 there were Tinea pedis 230 cases ofin Tulungagung. The case occurred because the community was not well informed and understood about Tinea Pedis. The purpose of this study was to determine the effect of health education aboutdisease Tinea Pedis on the attitude of farmers in the prevention ofdisease Tinea Pedis in Sukodono Village, Karangrejo District, Tulungagung Regency. The research design was One-Group Pre-post Test Design. The study population was all farmers in Sukodono Village. The number of samples was 79 people selected by purposive sampling technique. Data was taken using a questionnaire sheet. Data is processed bytechniques Editing, Coding, Scoring and Tabulating. Data analysis with Wilcoxon statistical test . The results showed that before counseling only 30 respondents (38%) had good attitudes and after counseling there were 53 respondents (67%) who had good attitudes. The results of statistical tests show that there is an influence of health education on changes in attitudes of farmers in Sukodono Village (p = 0,000 Î± = 0.05). Providing health information is very important to be carried out continuously, especially among farmers. This proved useful to change the attitude of farmers in the prevention and control of cases of Tinea pedis